Reduced brain reward response during cooperation in first-degree relatives of patients with psychosis: an fMRI study. Issue 16 (December 2014) - Gromann, P. M.; Shergill, S. S.; de Haan, L.; Meewis, D. G. J.; Fett, A.-K. J.; Korver-Nieberg, N.; Krabbendam, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. Psychosis is characterized by a profound lack of trust and disturbed social interactions. Investigating the neural basis of these deficits is difficult because of medication effects but first-degree relatives show qualitatively similar abnormalities to patients with psychosis on various tasks. This study aimed to investigate neural activation in siblings of patients in response to an interactive task. We hypothesized that, compared to controls, siblings would show (i) less basic trust at the beginning of the task and (ii) reduced activation of the brain reward and mentalizing systems. Method. Functional magnetic resonance imaging (fMRI) data were acquired on 50 healthy siblings of patients with psychosis and 33 healthy controls during a multi-round trust game with a cooperative counterpart. An a priori region-of-interest (ROI) analysis of the caudate, temporoparietal junction (TPJ), superior temporal sulcus (STS), insula and medial prefrontal cortex (mPFC) was performed focusing on the investment and repayment phases. An exploratory whole-brain analysis was run to test for group-wise differences outside these ROIs. Results. The siblings' behaviour during the trust game did not differ significantly from that of the controls. At the neural level, siblings showed reduced activation of the right caudate during investments, and the left insula during repayments. In addition, the whole-brain analysis revealed reduced putamen activation in siblings during investments. Conclusions. The findings suggest that siblings show aberrant functioning of regions traditionally involved in reward processing in response to cooperation, which may be associated with the social reward deficits observed in psychosis.